Self-Efficiency and Quality of Life Coronary Heart Disease Patients: A descriptive study - Wistiani, Ni Made Dewi; Puspawati, Ni Luh Putu Dewi; Pamungkas, M. Adreng (Future Science, 2022)
Introduction: Coronary heart disease is a disease that requires treatment in the long term and even for life, a strict diet, and restriction of physical activity which directly affects the patient's quality of life. Self-efficacy is one factor that affects the patient 's quality of life with coronary heart disease. Methods: This study aimed to determine the relationship between self-efficacy and quality of life of patients with coronary heart disease at the Cardiology Polyclinic at Sanglah Hospital Denpasar. This study used a correlational analytic design with a cross-sectional approach, a cardiac self-efficacy questionnaire, and the WHOQOL BREF. The sample size was 164 respondents recruited by consecutive sampling technique. Result: Most respondents were in the moderate self-efficacy category of 80 respondents (48.8 %), and most had a moderate quality of life, namely 64 respondents (39.0 %). Conclusion: High self-efficacy will increase the ability of coronary heart disease patients to follow a programmed therapy regimen, adhere to the recommended diet program, and regulate physical activities optimally so that they will be able to maintain and improve their quality of life